PERSENTASE BAGIAN-BAGIAN KARKAS ITIK LOKAL JANTAN YANG RANSUMNYA DITAMBAH LARUTAN DAUN SIRIH (PIPER BETLE LINN) DAN BUNGA KECOMBRANG (ETLINGERA ELATIOR) - Solihin, Solihin; Handarini, Ristika; Dihansih, elis (Universitas Djuanda Bogor, 2018)
This study was aimed at assessing the effects of the inclusion of piper betle leaf and torch ginger flower solution in commercial ration on the percentages of carcass and its parts of male local ducks. The study was conducted from June to August 2016 at Poultry Laboratory of Animal Science Study Program, Faculty of Agriculture, Djuanda University, Bogor. Twenty-four male local ducks aged 2 weeks with average initial body weight of 450 ± 53.04 g were used. A completely randomized design with 4 treatments and 3 replicates was used. Treatments consisted of 100% commercial ration (R0), commercial ration +2.5% piper betle leaf solution + 2.5% torch ginger flower solution (R1), commercial ration+ 5.0% piper betle leaf solution+ 2.5% torch ginger flower solution (R2), and commercial ration + 7.5% piper betle leaf solution + 2.5% torch ginger flower solution (R3). Measurements were taken onlive weight, the percentages of carcass, breast, wings, thigh, and back. Data were subjected to an analysis of variance and a Duncan test. Results showed that the inclusion of piper betle leaf and torch ginger flower solution in the rations of male local ducks gave significant effects (P<0.05) on the percentages of wings and thigh. Treatments were also found to maintain the percentages of breast and back. The inclusion of 2,5% piper betle leaf solution and 2,5% torch ginger flower solution in ration was also found to increase the percentage of thigh of male local ducks. It was recommended that 2,5% piper betle leaf and torch ginger flower solution be included in ration to result in higher percentages of and more economical wings and thigh.Key words: Betle leaf, ginger flower , male local duck, percentage of thigh.